2012
DOI: 10.1177/0954409712440397
|View full text |Cite
|
Sign up to set email alerts
|

Long co-planar mode III fatigue crack growth under non-proportional mixed mode loading in rail steel

Abstract: Fatigue tests have been performed to obtain the co-planar crack growth rate in rail steel under non-proportional mixed mode I and mode III cycles. In addition, a finite element analysis (FEA) has been performed to investigate the crack growth behaviour under this loading. The experiments showed that a long co-planar crack could be produced under this loading. Based on fracture surface observations obtained using a scanning electron microscope and FEA, the long coplanar crack growth was thought to be driven mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Several experimental studies, motivated by similar rolling contact fatigue crack growth problems, were devoted to fatigue crack growth under sequential mode I + II [2,[7][8][9][10][11] or sequential mode I + III [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies, motivated by similar rolling contact fatigue crack growth problems, were devoted to fatigue crack growth under sequential mode I + II [2,[7][8][9][10][11] or sequential mode I + III [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…WT exhibited the fastest coplanar FCG rates and, among the rail steels, the rates for RP were higher than those for RF when plotted against their appropriate equivalent SIF ranges, for both loading cases. Furthermore, Akama and Kiuchi [11] reported that FCG rates in RP under these two loading conditions (mixed modes I/II and I/III) were almost equal when plotted against the SIF ranges considered to be the main driving forces, ∆K II and ∆K III for the mixed mode I/II and I/III loading conditions, respectively. Therefore, the mechanism of shear-mode FCG under non-proportional mixed mode loadings that were subject to the RCF cracks can be considered to be the same even if the main crack driving force is in-plane shear or out-of-plane shear.…”
Section: Discussionmentioning
confidence: 95%
“…In the calculation results, both ∆σ max and ∆τ max planes were slightly oriented toward the ϕ direction within 7 • for all cases. First, the maximum tangential stress range was investigated to elucidate the effect of δ on crack branching direction [11]. The analysis was suggested to be based on an elasto-plastic stress field [21].…”
Section: Planes Of Maximum Normal and Shear Stress Rangesmentioning
confidence: 99%
See 2 more Smart Citations